Strategi Pembelajaran Ekspositori - Ika Guswanti; Ririn Restu Wirdani; Gusmaneli . (CV. ITTC INDONESIA, 2026)
This study aims to examine expository teaching strategies in Islamic Religious Education (PAI), covering their definition, characteristics, advantages and disadvantages, as well as implementation steps. The method used is a literature study (library research) by analyzing various relevant sources. The findings indicate that the expository teaching strategy is a teacher-centered approach, delivering material verbally, systematically, and in a structured manner to achieve optimal mastery of the content. This strategy has the advantage of delivering a wide range of material in a relatively short time and facilitates understanding of concepts, but it has weaknesses such as low active participation of students and communication that tends to be one-way. The implementation of the expository strategy is carried out through several stages, namely preparation, presentation, correlation, generalization, and application. Thus, this strategy is effective for learning that emphasizes mastery of concepts, while still taking into account the characteristics of students and learning objectives.